2018
DOI: 10.1021/acsnano.8b03962
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry on Stretchable Nanocomposite Electrodes: Dependence on Strain

Abstract: Stretchable nanocomposite conductors are essential for engineering of bio-inspired deformable electronics, human−machine interfaces, and energy storage devices. While the effect of strain on conductivity for stretchable conductors has been thoroughly investigated, the strain dependence of multiple other electrical-transport processes and parameters that determine the functionalities and biocompatibility of deformable electrodes has received virtually no attention. The constancy of electrochemical parameters at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…tretchable supercapacitors, enabling desirable portable and wearable electronics applications incapable of using conventional rigid electronics, are highly desirable [1][2][3][4][5][6][7][8][9][10] . Although conventional electrodes for supercapacitors are usually not stretchable or superelastic, the engineering of conventional electrodes with geometrically engineered structures provides notable breakthroughs for the achievements of stretchable and foldable devices [11][12][13][14][15] .…”
mentioning
confidence: 99%
“…tretchable supercapacitors, enabling desirable portable and wearable electronics applications incapable of using conventional rigid electronics, are highly desirable [1][2][3][4][5][6][7][8][9][10] . Although conventional electrodes for supercapacitors are usually not stretchable or superelastic, the engineering of conventional electrodes with geometrically engineered structures provides notable breakthroughs for the achievements of stretchable and foldable devices [11][12][13][14][15] .…”
mentioning
confidence: 99%
“…To the best of our knowledge, this device presented the highest electrochemical performance for a fully-integrated stretchable carbon-based device (Table S4, Supporting Information). The influence of the scan rate (10-200 mV s −1 ) in the presence of Fe(CN) 6 3−/4− ions is shown in Figure 2h,i. Well-defined cyclic voltammograms were observed in all scan rates, as shown in Figure 2h, indicating that peak current of the voltammograms has a linear behavior as a function of square root of scan rate (ν 1/2 ), indicating that the redox process is diffusion controlled, [33] as confirmed in Figure 2i and discussed in Figure S12, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…d) Cyclic voltammograms for (i) control and before (-) and after (-) stretching levels. Cyclic voltammograms were obtained in the presence of 5 × 10 −3 m Fe(CN) 6 3−/4− ions in KCl 0.5 m, scan rate for d(i-iv) was 30 mV s −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies reported similar electrochemical behavior during stretching, due to the expansion of the printed composite material, most of the 2D tortuous structure still experience a significant drop in conductivity, hence impeding the overall device stability during deformations. [ 28,86 ] Depending on the quality of the stretchable ink and the substrate used, hysteresis effect has also been reported, where the conductivity of the printed inks changes temporally due to the viscoelastic behavior of the polymers and polymer composites. [ 87 ]…”
Section: Tortuous 2d Designsmentioning
confidence: 99%